#MeToo dans l’édition : tout le monde savait - Un collectif de plus de 100 personnalités de l'édition (Libération, 2021)
Plus d’une centaine de femmes travaillant dans le livre signent un texte dénonçant un climat délétère et des inégalités flagrantes. Elles demandent que les entreprises de l’édition prennent leur responsabilité.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; europe; france; inégalités; metoo; patriarcat; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail; violences; violences sexistes et sexuelles

Women and burnout in the context of a pandemic - Aldossari, Maryam; Chaudhry, Sara (Gender, Work & Organization, 2021)
This article presents the lived narrative of a female academic with children working in a British university and trying to cope with a completely new way of work and life in the context of the pandemic. The overall aim of the article is to offer a gendered account of burnout—specifically how women may be experiencing burnout at multiple levels, and the efficacy of their subsequent coping strategies. The narrative provides insights into how a range of coping mechanisms such as disengagement, denial, and energy conservation are deployed to deal with the increased responsibilities at work and home as a result of the pandemic. Existing research has viewed burnout as gender neutral, leaving a gap in the literature on the significant differences in both men's and women's experience of burnout as well as their coping behaviors.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; burn-out; charge mentale; division sexuelle du travail; double journée de travail; europe; inégalités; maternité; privilèges; projet charge mentale; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; santé; systèmes d'oppressions; thématiques; travail